Measuring The Accomodation of Sharia Principles in Determining the Pricing of Consumer Financing Products of BSM (Sharia Mandiri Bank) - Syaparuddin Syaparuddin (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2017)
This study is intended to evaluate the pricing determination of consumer financing products of BSM, so that the customers can find out if BSM provides a treatment of installment payments on consumer financing products in accordance with sharia principles. In establishing the pricing on consumer financing products, BSM uses two methods, namely: the annuity method and the proportional (flat) method. The Construction of pricing on the consumer financing products in BSM is based on: (a) the total of installment payment per-month, it is based on financing platfond, percentage of margin, and period of time, (b) the principal installment payment per-month, it is based on total of principal installment payment per-month, and margin, (c) the installment payament of profit margin per-month, it is based on platfond, principal, and percentage of margin. The pricing used by BSM needs to be revitalized because (a) there is a profit return factor for customers, (b) containing a gharar element, and (c) using the paradigm of conventional bank in setting pricing.